(untitled) (REVISTA NODO, 2015)
Two experiences related to the colonization off the coast of Aysen, central region of Patagonia Chilean, shown as a landscape features sublime architectural utopias could catalyze oriented incorporate that geography still uninhabited in the territory and the Chilean imaginary: A fisheries based on the peninsula of San Quintin, Project title Emilio Duhart, and the boat Amereida, School of Architecture UCV. The first, from the coast inland, proposed a systematic logic to fill the territory from the reuse of burned forests. The second envisaged a form of occupation around the fjords that penetrate the territory mountainous region. In both projects, pragmatic and utopian one another pragmatically utopian, the peculiar geography of the coast Patagonian inspired ideas on how to build the future of southern Chile, taking a stand critical of territorial policies that in their respective time period he was trying to turn the central Patagonia of “land” no national space. Reflect on these experiences helps to understand how the development of the Chilean architecture can He has articulated with the history of the conquest of its internal borders and political speeches and culture associated with them.